2006
DOI: 10.1016/j.febslet.2006.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Human RELMβ is a mitogenic factor in lung cells and induced in hypoxia

Abstract: RELMb (resistin-like molecule) represents the most related human homologue of mouse RELMa, also known as hypoxic-induced mitogenic factor (HIMF). In this study, we isolated RELMb cDNA from human lung tissue and performed regulatory and functional expression studies. RELMb mRNA was upregulated in hypoxia in human lung A549 cell line as well as primary cultured adventitial fibroblasts and smooth muscle cells (SMC) of pulmonary arteries. Upon transfection of a RELMb encoding expression plasmid into these cells, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 12 publications
2
48
0
Order By: Relevance
“…The dilated crypt structures lined with isolated goblet cells suggest that, in the absence of RELMβ, the colonic epithelium and its associated crypt structures may either be better able to survive destruction or may be more rapidly reconstituted in the setting of intestinal inflammation. Although recent evidence that RELMβ acts as a mitogenic factor in lung epithelium via a PI3K-dependent mechanism might be consistent with this notion (21), there was no difference in epithelial apoptosis, which was very rare, as determined by TUNEL staining, in both wild-type and RELMβ -/-mice that received DSS (data not shown). Alternatively, the RELMβ-null mice may be more resistant to the initiation of disease induced by DSS.…”
Section: Figuresupporting
confidence: 53%
“…The dilated crypt structures lined with isolated goblet cells suggest that, in the absence of RELMβ, the colonic epithelium and its associated crypt structures may either be better able to survive destruction or may be more rapidly reconstituted in the setting of intestinal inflammation. Although recent evidence that RELMβ acts as a mitogenic factor in lung epithelium via a PI3K-dependent mechanism might be consistent with this notion (21), there was no difference in epithelial apoptosis, which was very rare, as determined by TUNEL staining, in both wild-type and RELMβ -/-mice that received DSS (data not shown). Alternatively, the RELMβ-null mice may be more resistant to the initiation of disease induced by DSS.…”
Section: Figuresupporting
confidence: 53%
“…Furthermore, mouse RELMα and its human homologue, RELMβ, are known as hypoxia-induced mitogenic factors and are smooth muscle cell mitogens. 48,[57][58][59][60] As an explanation for our unexpected data, the role of RELMα in arterial thickening and remodeling could vary depending on the type of challenge (e.g., hypoxia vs. antigen). 48,61 Comparing the data shown in Figures 5 and 6 suggests that airway eosinophils, neutrophils, myeloid cell activation markers S100a8 and S100a9, and IL-6 are not critical promoters of the severe arterial remodeling response and that IFN-γ is not a critical inhibitor.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study has suggested that human RELM␤ also has mitogenic action on human lung cells, and this protein may contribute to pulmonary vascular remodeling and fibrotic lung disease (30). Considering the limitations of current treatment of PH (9), inhibition of HIMF might be considered to prevent or reduce lung inflammation as well as hypoxia-induced PH.…”
Section: Discussionmentioning
confidence: 99%